Estudio de factibilidad para la creación de un centro de acopio de leche cruda en la comunidad de Rasuyacu, de la parroquia Toacaso, del cantón Latacunga, provincia de Cotopaxi - Musuña Tipantuña, Carmen Elisa (2023)
The dairy sector has several problems in the country, which occur especially in both In the field of production, distribution and also consumption, one of the main ones is the variation in prices caused to the milk producer, in the case of the Rasuyacu community, an agricultural and livestock community whose main source of income is the sale of milk, which is sold to intermediaries causing damage to the producers, that is the need for the community to seek to strengthen its organization and deal with this problem by building the collection center.